2016
DOI: 10.1097/gox.0000000000001029
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Models of Cleft Palate Pathology for Surgical Education

Abstract: Objective:To explore the potential viability and limitations of 3D printed models of children with cleft palate deformity.Background:The advantages of 3D printed replicas of normal anatomical specimens have previously been described. The creation of 3D prints displaying patient-specific anatomical pathology for surgical planning and interventions is an emerging field. Here we explored the possibility of taking rare pediatric radiographic data sets to create 3D prints for surgical education.Methods:Magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 24 publications
0
47
0
3
Order By: Relevance
“…3D printing is becoming a valuable resource in the world of medical and anatomical education, thanks to the ability to cheaply, efficiently, and rapidly reproduce complex relationships between structures. 14,15 To prove the versatility of this technology, educators have reproduced cadaveric limb segments, cranial sinuses, vascular structures, 16 orbital dissections, 17 pediatric laryngeal and cleft palate simulators, 18,19 training set ups for surgical valve replacement, 11 arterial access simulations, 12 and bronchial trees for simulated bronchoscopy. 20,21 This ability to reproduce complex structures with high fidelity for manipulation and examination has also made 3D printing an attractive modality in cardiology.…”
Section: Discussionmentioning
confidence: 99%
“…3D printing is becoming a valuable resource in the world of medical and anatomical education, thanks to the ability to cheaply, efficiently, and rapidly reproduce complex relationships between structures. 14,15 To prove the versatility of this technology, educators have reproduced cadaveric limb segments, cranial sinuses, vascular structures, 16 orbital dissections, 17 pediatric laryngeal and cleft palate simulators, 18,19 training set ups for surgical valve replacement, 11 arterial access simulations, 12 and bronchial trees for simulated bronchoscopy. 20,21 This ability to reproduce complex structures with high fidelity for manipulation and examination has also made 3D printing an attractive modality in cardiology.…”
Section: Discussionmentioning
confidence: 99%
“…There are examples already where the use of printed anatomical structures in surgical training has been explored for pediatric surgery for cleft palate pathologies by authors of the current study (Lioufas et al, 2016), and developmental abnormalities of the ear, where surgery may involve both soft and hard tissues and close proximity to facial nerves (Barber et al, 2016). With access to digital data spanning a broad spectrum of fetal ages, the underlying data developed in the present study can be translated into several different printed formats, including multimaterial prints and 3D print-guided multimaterial simulators for practicing fetal surgery on 3D prints at appropriate stages of human development, as has been done for neurocranial surgical simulation (amongst other applications) (Waran et al, 2014;Ryan et al, 2016Ryan et al, , 2015Tai et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…3D printing technology is becoming increasingly involved in the current era of delivering medical care and is being applied towards creating personalized prosthetics, 3D printed surgical instruments, medical student and resident education, and patient-speci c anatomical models to help guide surgeons preoperatively and intraoperatively [1][2][3][4][5][6][7]. Previous studies have demonstrated the possibility of producing cost-effective yet robust 3D printed surgical retractors that far exceed the threshold for clinically excessive retraction in the operating room even after autoclave sterilization [6,8].…”
Section: Introductionmentioning
confidence: 99%